Design, synthesis and evaluation of flurbiprofen-clioquinol hybrids as multitarget-directed ligands against Alzheimer's disease. Issue 7 (1st April 2020) - Yang, Ziyi; Song, Qing; Cao, Zhongcheng; Yu, Guangjun; Liu, Zhuoling; Tan, Zhenghuai; Deng, Yong
Graphical abstract: Abstract: A series of novel flurbiprofen-clioquinol hybrids were designed and synthesized as multifunctional agents for Alzheimer's disease therapy, and their potential was evaluated through various biological experiments. In vitro studies showed that most target compounds exhibited significant ability to inhibit self- and Cu 2+ -induced β -amyloid aggregation. Furthermore, some target compounds, especially 7i and 7r, also showed biometal chelating abilities, antioxidant activity, anti-neuroinflammatory activity and appropriate BBB permeability. These biological activities indicated that the representative compound 7i and 7r might be promising multifunctional agents for AD treatment.